Pengaruh Persepsi Penggunaan, Efisiensi, Efektif terhadap Kemudahan Pemesanan E-Ticketing Kereta Api - Dwijayani, Henny; Septian, Javis Ragil; Harinie, Luluk Tri (Universitas Darul Ulum, 2022)
This study was conducted to examine the effect of perceived use, efficiency, and effectiveness on the ease of ordering train e-ticketing. The level of acceptance of technology can be known and analyzed using TAM theory. The analytical method used to examine the effect of perception is partial multiple linear regression where respondents numbered 128 and some accompanying characteristics. Data collection techniques in the form of questionnaires and measurement of data using a Likert scale. The study results stated that train service users considered that the existence of an application and ticket booking through e-ticketing provided convenience in ordering train tickets. Besides being easy to use, it is also effective because of the several amenities it offers. However, other results show that they are different, namely efficient, where e-ticketing does not offer a cheaper price, meaning that the price is the same as ordering tickets manually.